Digital labour in Central and Eastern Europe: Evidence from the ETUI internet and platform work survey - Agnieszka Piasna; Jan Drahokoupil (European Trade Union Institute (ETUI), 2019)
This working paper presents the results of the ETUI Internet and Platform Work Survey conducted in Bulgaria, Hungary, Latvia, Poland and Slovakia in 2018-2019. The objective is to map the extent of digital labour in central and eastern Europe (CEE). We analyse two types of online sources for generating income: internet work; and its subset, platform work. We find that past experiences with generating income on the internet are relatively common among working age adults. However, the prevalence of regular internet and platform work remains very low in all five CEE countries; indeed, lower according to our estimates than in other comparative surveys. We attribute the differences to the inconsistent quality of non-representative samples of internet users that were deployed in other studies and, in particular, the use of paid, opt-in online surveys which themselves are examples of online gig work. We do not find evidence that internet and platform work is creating a qualitatively new labour market that encroaches on traditional age and gender segmentation. Neither is it a market of 'student jobs'. Moreover, the labour market situation of internet and platform workers was somewhat more precarious than that for employed people generally, with a higher incidence of non-standard and fragmented employment. Finally, services requiring higher skills and creativity were among the least prevalent forms of internet work, suggesting little overlap with the knowledge-based economy.
Keywords: 330; work design; Internet; labor market research; Eastern Europe; Arbeitsgestaltung; Internet; Arbeitsmarktforschung; Osteuropa